2023
DOI: 10.1186/s13054-023-04421-w
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastometry-guided haemostatic resuscitation in severely injured patients: a propensity score-matched study

Abstract: Background To accelerate the diagnosis and treatment of trauma-induced coagulopathy (TIC), viscoelastic haemostatic assays (VHA) are increasingly used worldwide, although their value is still debated, with a recent randomised trial showing no improvement in outcome. The objective of this retrospective study was to compare 2 cohorts of injured patients in which TIC was managed with either a VHA-based algorithm or a conventional coagulation test (CCT)-based algorithm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Many, although not all, studies have demonstrated that treatment algorithms based on VET resulted in reduced transfusion requirements in TIC [20,29,[81][82][83][84][85][86]. Two studies in trauma patients that compared transfusion requirements before and after implementation of a TEG-guided resuscitation protocol reported significantly lower RBCs and FFP transfusion rates [82,83].…”
Section: The Effect Of Viscoelastic Test On Allogenic Blood Transfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many, although not all, studies have demonstrated that treatment algorithms based on VET resulted in reduced transfusion requirements in TIC [20,29,[81][82][83][84][85][86]. Two studies in trauma patients that compared transfusion requirements before and after implementation of a TEG-guided resuscitation protocol reported significantly lower RBCs and FFP transfusion rates [82,83].…”
Section: The Effect Of Viscoelastic Test On Allogenic Blood Transfusionmentioning
confidence: 99%
“…In a retrospective study, David et al reported that fewer patients treated according to ROTEM test results received massive transfusions compared to patients treated based on SCT results (15% vs. 42%, P < 0.01). No significant difference was observed in mortality rates [86]. 'The reversal of trauma-induced coagulopathy study' (RETIC) included trauma patients with established TIC according to predefined ROTEM criteria (FIBTEM A10 < 9 mm or EXTEM CT > 90 s) [20].…”
Section: The Effect Of Viscoelastic Test On Allogenic Blood Transfusionmentioning
confidence: 99%
“…TIC is associated with impaired outcomes, including an increased likelihood of massive bleeding, multiple organ failure, transfusion, and death in the first hours following hospital admission [ 3 5 ]. Early and aggressive resuscitation strategies that aim to directly correct TIC are associated with improved outcomes and decreased blood products administration [ 6 , 7 ], and therefore the early identification and prompt treatment of TIC are essential [ 8 ]. However, in daily practice, the administration of hemostatic resuscitation is often based on clinical judgment, which performs moderately to identify massive hemorrhage [ 9 ], leading to unnecessary blood product administration to patients responsible for potential side effects and wasted blood products [ 10 ].…”
Section: Introductionmentioning
confidence: 99%